SISTEM PAKAR DIAGNOSIS PENYAKIT HEWAN SAPI DENGAN METODE FORWARD CHAINING - Muh. Abdi Fahmi; Ika Purwanti Ningrum; Jayanti Yusmah Sari (Informatics Engineering Department of Halu Oleo University, 2018)
The cow is a livestock that has a lot of economic potentials is quite promising. Diseases in cattle can be transmitted quickly and can result in death. The disease can be caused by bacteria, viruses, fungi, and parasite. To prevent cattle disease is not contagious, then the owner of the cow must know first about the diseases in cattle, so it can be done prevention and treatment of cattle as early as possible.The expert system is a system designed to imitate an expert’s expertise in solving an existing problem. Knowledge of veterinary diseases is drawn up about literature and interviews with veterinarians about veterinary disease used to diagnose disease-disease illness and how to treat it.Determination of disease in this expert system is done through a consultation process between users with the system and also use Forward Chaining method. The system will display symptoms of the disease, then the user selected symptoms experienced. User-selected symptoms will be adjusted to the existing rule so that users will get the diagnosis of symptoms, types of disease and treatment solutions. It is expected that this expert system can provide information and treatment early if the cattle are detected to experience pain. Keywords: Cow Disease, Expert System, Forward Chaining.DOI :10.5281/zenodo.1673278